Cyano-bridged homodinuclear copper(II) complexes - Atanasov, Mihail; Comba, Peter; Hanson, Graeme R.; Hausberg, Sascha; Helmle, Stefan; Wadepohl, Hubert (Inorganic chemistry, 2011)
The synthesis and structural analysis (single crystal X-ray data) of two mononuclear ([Cu(L1)(CN)]BF4 and [Cu(L3)(CN)](BF4)) and three related, cyanide-bridged homodinuclear complexes ([{Cu(L1)}2(CN)](BF4)3·1.35 H2O, [{Cu(L2)}2(CN)](BF4)3 and [{Ni(L3)}2(CN)](BF4)3) with a tetradentate (L1) and two isomeric pentadentate bispidine ligands (L2, L3; bispidines are 3,7-diazabicyclo[3.3.1]nonane derivatives) are reported, together with experimental magnetic, electron paramagnetic resonance (EPR), and electronic spectroscopic data and a ligand-field-theory-based analysis. The temperature dependence of the magnetic susceptibilities and EPR transitions of the dicopper(II) complexes, together with the simulation of the EPR spectra of the mono- and dinuclear complexes leads to an anisotropic set of g- and A-values, zero-field splitting (ZFS) and magnetic exchange parameters (Cu1: gz = 2.055, gx = 2.096, gy = 2.260, Az = 8, Ax = 8, Ay = 195 × 10-4 cm-1, Cu2: g and A as for Cu1 but rotated by the Euler angles α = −6°, β = 100°, Dexc = −0.07 cm-1, Eexc/Dexc = 0.205 for [{Cu(L1)}2(CN)](BF4)3·1.35 H2O; Cu1,2: gz = 2.025, gx = 2.096, gy = 2.240, Az = 8, Ax = 8, Ay = 190 × 10-4cm-1, Dexc = −0.159 cm-1, Eexc/Dexc = 0.080 for [{Cu(L2)}2(CN)](BF4)3). Thorough ligand-field-theory-based analyses, involving all micro states and all relevant interactions (Jahn-Teller and spin-orbit coupling) and DFT calculations of the magnetic exchange leads to good agreement between the experimental observations and theoretical predictions. The direction of the symmetric magnetic anisotropy tensor Dexc in [{Cu(L2)}2(CN)](BF4)3 is close to the Cu···Cu vector (22°), that is, nearly perpendicular to the Jahn-Teller axis of each of the two CuII centers, and this reflects the crystallographically observed geometry. Antisymmetric exchange in [{Cu(L1)}2(CN)](BF4)3·1.35 H2O causes a mixing between the singlet ground state and the triplet excited state, and this also reflects the observed geometry with a rotation of the two CuII sites around the Cu···Cu axis.